STRATEGI MANAJEMEN SUMBER DAYA MANUSIA INTERNASIONAL DALAM MENGHADAPI KOMPLEKSITAS, KRISIS, DAN RISIKO GLOBAL - Journal, Berajah; Faddel Muhammad, Haiqal; Erisyadi, Yusup; Ruslan, Burhanudin; Doriomas, Utari (CV. Lafadz Jaya, 2025)
In the dynamic era of globalization, international human resource management (IHRM) faces complex challenges arising from interconnected economic, political, and social crises. The global economic crisis impacts workforce structures through restructuring, cost reduction, and changes in working conditions. Political crises, marked by nationalistic policies and labor mobility restrictions, hinder the flow of global talent. Meanwhile, social crises driven by demographic changes and international migration require HR to manage cultural diversity and social integration in the workplace. In this context, IHRM must develop adaptive and flexible strategies to navigate uncertainties and maximize the potential of the global workforce. Effective strategies include managing talent mobility, developing cross-cultural competencies, and leveraging digital technologies to support decision-making and communication. This holistic approach enables HR to act as a strategic partner for organizations in managing risks and capitalizing on opportunities amid rapid and uncertain global changes. Consequently, IHRM can help organizations survive and thrive in facing complex challenges and global crises.